Arterial Stiffness and Renal Replacement Therapy: A Controversial Topic. (7th May 2015) - Fischer, Edmundo Cabrera; Zócalo, Yanina; Galli, Cintia; Wray, Sandra; Bia, Daniel
Abstract : The increase of arterial stiffness has been to have a significant impact on predicting mortality in end-stage renal disease patients. Pulse wave velocity (PWV) is a noninvasive, reliable parameter of regional arterial stiffness that integrates the vascular geometry and arterial wall intrinsic elasticity and is capable of predicting cardiovascular mortality in this patient population. Nevertheless, reports on PWV in dialyzed patients are contradictory and sometimes inconsistent: some reports claim the arterial wall stiffness increases (i.e., PWV increase), others claim that it is reduced, and some even state that it augments in the aorta while it simultaneously decreases in the brachial artery pathway. The purpose of this study was to analyze the literature in which longitudinal or transversal studies were performed in hemodialysis and/or peritoneal dialysis patients, in order to characterize arterial stiffness and the responsiveness to renal replacement therapy.